TI_GERICHTE 52.2012.276 vom 11. Oktober 2013 , Licenza edilizia per uno stabile unifamiliare. Nucleo di villaggio. Ricostruzione. Contiguità. - TI Tribunale d'appello (2013)
Licenza edilizia per uno stabile unifamiliare. Nucleo di villaggio. Ricostruzione. Contiguità.